EFEKTIFITAS EKSRAK DAUN PEPAYA SEBAGAI PENGHAMBAT JAMUR Fusarium PENYEBAB REBAH KECAMBAH PADA CABAI MERAH (Capsicum annum L.) - Sagita, Yelin; Haryuni; Eko Fransiko; Adnan; Parwito, Parwito (Fakultas Pertanian Universitas Ratu Samban, 2023)
big chili (Capsicum year L.) is an important vegetable commodity in Indonesia which is widely used as a cooking flavouring. In addition to protein, fat and carbohydrate nutrients, large chilies also contain vitamins A, B1 and vitamin C which are substances needed for human health (Prayudi , 2010). Red chili production in Indonesia in 2019 amounted to 12,144,1900 tons with a harvested area of ​​133,434 hectares and in Bengkulu province 378,1200 tons with a harvested area of ​​6,489 hectares. Whereas in 2020 in Indonesia it was 12,641,9000 tons with a harvested area of ​​133,434 ha and red chili production in Bengkulu reaching 396,3800 tons per 6,510 hectares (Central Bureau of Statistics, 2020). Judging from the data above, chili production in Indonesia will increase in 2020 and Bengkulu province will also experience an increase in 2020.This research will be carried out from June to July 2022, the research location is in Meranti Jaya Village, Ujan Mas District, Kepahiang Regency, Bengkulu Province. The research method used was a completely randomized design (CRD) with 1 treatment factor, namely papaya leaf extract consisting of 5 levels with 3 replications and each replication consisted of 10 samples, with a dose of p0 = 0 ml/liter of water, p1 = 10 ml/liter of water, p2= 15 ml/liter of water, p3= 20 ml/liter of water, p4= 25 ml/liter of water. The number of plants in the study was P x T x U = 5 x 10 x 3 = 150 plants. Based on the results of variance, it is known that the concentration of papaya leaf extract p1 and p2 has shown a decrease in fungal attackFusarium oxysporum but the inhibitory effect was stronger at concentrations of p3 and p4. it proves that papaya leaf extract has an anti-fungicidal effect against fungiFusarium oxysporum.The research showed that the lower the concentration of the extract given, the less the inhibitory power and the less anti-fungal content, and vice versa if the concentration of the extract given is higher, the anti-fungal content in the extract can be sufficient in inhibiting the growth of the fungus Fusarium oxysporum. So it can be concluded that there was a significant effect on the application of papaya leaf extract in inhibiting the growth of the fungus Fusarium oxysporum and the most effective doses in inhibiting the fungus Fusarium oxysporum were p3 and p4.